Climate Change Impacts on Birth Outcomes in Brazil - Paula Carvalho Pereda; Tatiane Menezes; Denisard C. O. Alves (Inter-American Development Bank (IDB), 2014)
This paper attempts to identify the climatic effect on birth outcomes in Brazil and, thus, to predict the potential impact of climate change. Panel data models indicate that excess and lack of rainfall have the most important harmful effects on newborns' health; temperature stresses and low relative humidity also have effects. The use of climate change forecasts for Brazil suggests a possible increase of 305 neonatal deaths annually and, for families in the Primary Care Program, three thousand additional low-weight births each year. The paper further examines public policy's role in minimizing the effects of extreme weather. Mothers' education, sanitation access and health care assistance to pregnant women represent the main instruments for addressing neonatal health problems
hdl:11319/6451
Keywords: I12; I18; Q54; 330; Neonatal mortality; Health economics; Panel data; Climate change impacts on health